2020
DOI: 10.3390/ijfs8010004
|View full text |Cite
|
Sign up to set email alerts
|

Existence of the Audit Expectation Gap and Its Impact on Stakeholders’ Confidence: The Moderating Role of the Financial Reporting Council

Abstract: This paper empirically emphasizes the existence of the audit expectation gap and its impact on stakeholders’ confidence, moderated by the active role of the financial reporting council. As a maiden attempt to portray the relationship, a higher-order model has been constituted and assessed with the pragmatic exploration, smearing the partial least squares structural equation model (PLS-SEM). The data contains 174 respondents as auditors, investors, investment and credit analysts, and regulatory agencies in Bang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 73 publications
0
37
0
3
Order By: Relevance
“…An attempt had been made in carrying out a detailed review of auditing concepts and stakeholders' expectation from the perspective of the fundamental and indispensable economic roles of auditing in providing expert service to the generality of stakeholders, instilling confidence of block-building of reinstating and reinforcing eroded trust and confidence in audit reports and financial reporting (Akther & Xu, 2020). The auditing concepts have lost their focus and relevance due to some reported carefree and unprofessional reckless disposition by some auditors involving some cases of financial scandals in the likes of Enron and Arthur Andersen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An attempt had been made in carrying out a detailed review of auditing concepts and stakeholders' expectation from the perspective of the fundamental and indispensable economic roles of auditing in providing expert service to the generality of stakeholders, instilling confidence of block-building of reinstating and reinforcing eroded trust and confidence in audit reports and financial reporting (Akther & Xu, 2020). The auditing concepts have lost their focus and relevance due to some reported carefree and unprofessional reckless disposition by some auditors involving some cases of financial scandals in the likes of Enron and Arthur Andersen.…”
Section: Discussionmentioning
confidence: 99%
“…The study results suggested the relative significance of more robust investor protection and legal framework and enforcement in establishing higher audit and earnings quality. Akther and Xu (2020) investigated the existence of the audit expectation gap and effect of expectation gap on stakeholders' confidence and dully moderated by the economic council's dynamic role. The study employed a pragmatic exploratory method, structured questionnaire to source data from selected respondents.…”
Section: Empirical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Audited financial reports can increase the confidence of users of financial statements in all financial information displayed in the financial statements and increase confidence in the services provided by company management. This Credibility Theory emphasizes the explanatory ability of information in financial statements to provide explanations that users of financial information can understand in order to make economic decisions (Eid, 2014;Akther & Xu, 2020).…”
Section: Theory Of Credibilitymentioning
confidence: 99%
“…According to the positions of Akpanuko and Umoren (2018); Linck, Netter, and Shu (2013), earnings management activities are illegal and deceitful in all forms, and investment decision using discretionary earnings may not add value to investment decision relying on them and could have litigation tendencies. Managers and corporate bodies who indulge in earnings management to increase earnings may not be too smart for too long and investors, shareholders, and the general the public cannot be fooled forever (Akther & Xu, 2020).…”
Section: Empirical Reviewmentioning
confidence: 99%